Installation of PLTS as a Source of Electricity for Enhancement of Chicken Farming Business in Percut Sei Tuan Sub-District Deli Serdang District: Pemasangan PLTS sebagai Sumber Listrik untuk Peningkatan Usaha Budidaya Ayam di Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Partaonan Harahap; Benny Oktrialdi; Rimbawati; Balisranislam (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The need for electrical energy at this time is very important for humans. Electrical energy is currently still using fossil fuels. Indonesia is a tropical country so it has excess sunlight. Utilization of sunlight can be used for solar power generation, solar power generation is one of the renewable energies where the use of sunlight can be converted into electrical energy. The intensity of sunlight and weather conditions can affect the voltage and current generated from solar panels. The magnitude of the value of the electric power generated by the 100 Wp solar panel is strongly influenced by weather conditions, the average test gets a maximum voltage and current of 13.41 V and 4.60 with an average voltage and current of 12.7 V and 2.7 A. For a load of equipment in 24 hours of use requires a power of 392 watts. It is hoped that the chicken breeder partners in Percut Sei Tuan District, Deliserdang Regency can apply PLTS technology to increase chicken livestock production.